APPLICATION ALGORITHM OF SUBSTRATE METABOLIC DRUGS IN THE EARLY PERIOD OF ACUTE ACETIC ACID POISONING - A. A. Stopnitsky; R. N. Akalaev; Yu. S. Goldfarb (Неотложная медицинская помощь, 2016)
ABSTRACT. Acute poisoning with acetic acid remains one of the most relevant pathologies in the structure of chemical injury. The article analyzes the use of metabolic drugs based succinic acid in complex intensive therapy at an early stage severe poisoning acetic acid. Proved that the use of these drugs significantly improves outcomes in patients with acetic acid acute poisoning by reducing the intensity of hemolysis of blood, as well as аntihypoxant, antioxidant and hepatoprotective properties of drugs.